PENERAPAN MONTESSORI DALAM PEMBELAJARAN MATEMATIKA MELALUI LURING SEBAGAI ALTERNATIF MASA PANDEMI - Sulha Sulha (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
Covid-19, which has hit all corners of the country, has made education policymakers to change the learning model by implementing health protocols, one of which is called offline learning. Montessori is a learning concept in accordance with daily activities that are experienced directly by students. This study aimed to describe the application of montessori in offline mathematics learning. The research method used qualitative descriptively. The subjects of the study were second-grade students of SD Negeri Karangren 1 in the 1st semester of the 2020/2021 school year. The results showed that good environmental support was needed to support the montessori methods in offline mathematics learning. This support includes the availability of the montessori apparatus and the willingness of parents to support learning.